EFFECT OF INTRAVITREAL PERFLUORO PROPANE (C3F8) IN THE MANAGEMENT OF SYMPTOMATIC VITREOMACULAR TRACTION - Syeda Minahil Gardezi,; Khujasta Gul,; Misbah Batool,; Ali Afzal Bodla, (Journal of Ayub Medical College Abbottabad, 2023)
Background: To study the efficacy of a single 0.3ml of C3F8 injection for the treatment of symptomatic VMT. Methods: In this retrospective interventional study a total of nine patients were recruited. The mean age was 67 years. Patients had a follow up at one week and four weeks post injections. VMT status was confirmed on repeat Oct scan. Results: There was a complete release of VMT In 4 patients after one week and further release of VMT was observed in two more patients after four weeks. Hence six out of nine patients had complete resolution of pathology following C3F8 injection. Conclusion: Intravitreal C3F8 is a cheaper and safer option for the treatment of vitreomacular traction as compared to pars plana vitrectomy or Ocriplasmin.